Enabling coastal blue carbon in Aotearoa New Zealand: opportunities and challenges - Stewart-Sinclair, Phoebe J.; Bulmer, Richard H.; Macpherson, Elizabeth; Lundquist, Carolyn J. (Frontiers in Marine Science, 2024)
Blue carbon is the carbon sequestered by coastal and marine habitats such as mangroves, saltmarsh, and seagrasses. The carbon sequestration service provided by these habitats could help to mitigate climate change by reducing greenhouse gas (GHG) emissions, as well as providing other important ecosystem services. Restoration of coastal habitats for the purpose of sequestering blue carbon can generate carbon credits, potentially offsetting the costs of restoration and any lost revenue for landowners. Coastal blue carbon projects have been successfully implemented overseas, but a blue carbon market has not yet been established in Aotearoa New Zealand (ANZ). Here we identify key data gaps that will be necessary to fill to develop a blue carbon market in ANZ. Calculation of carbon abatement through development of a standardised method is the first step and will allow economic assessment of potential restoration sites. Economic assessment will determine if the carbon credits generated will cover restoration costs and lost revenue from restored lands. Once economically feasible potential restoration sites have been identified, prioritisation of sites could be determined by the value of co-benefits produced (i.e., biodiversity). There are also legal uncertainties in ANZ and ownership of the foreshore has been a contentious topic. Current legislation provides that neither the Crown nor any other person owns or can own the common marine and coastal area, although Māori may apply for recognition of customary rights, interests, and title in the area.